Analisis Faktor-Faktor yang Mempengaruhi Jumlah Kematian Ibu dan Bayi di Provinsi Jawa Tengah Menggunakan Regresi Bivariat Poisson - Mutiara Widhika Astuti; A’yunin Sofro (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2018)
Maternal and infant mortality are two correlated subjects, because during pregnancy the mother's placenta distributes nutrients to the fetus so the baby born is affected by the condition of his mother. Central Java has significant maternal and neonatal mortality rates in Indonesia. In this case, need a research to analyze the factors that influence maternal and infant mortality using Bivariate Poisson Regression (BPR) method. BPR is the right method because it can reconfirm two data that are correlated with Poisson distribution. This study produced three models. The first model is the maternal mortality rate has several significant factors, including pregnant women implementing the K1 and K4 program, vitamin A to postpartum mothers, pregnant women getting Fe tablets, and midwifery handle complications. The second model is the infant deaths that have factors pregnant women implementing the K4 program, helped assistance by medical team, postpartum mothers receiving vitamin A, pregnant women getting Fe tablets, complications handled by midwifery, and KB participants. The final model involves maternal and infant mortality. Significant factors are pregnant women implementing the K1 program, pregnant women implementing the K4 program, giving vitamin A to postpartum mothers, and KB participants.